Synthesis and characterization of four novel 1,3-azole based push-pull heterocyclic systems - Raposo, M. Manuela M. (2017)
Four novel 1-(4-thiophene-2-yl)phenyl)-1H-pyrrole derivatives functionalized with different 1,3-azole moieties fused with a phenyl ring have been synthesized, in fair yields, and their optical properties studied. The results showed that the optical properties could be readily tuned by changing the electronic nature of the azole ring, or even with the introduction of a nitro group. The benzothiazole, benzimidazole and benzoxazole heterocycles are heteroaromatic electron deficient moieties that act as both acceptor groups and -conjugated spacers with auxiliary electron withdrawing ability.1 Moreover, benzimidazole derivatives offers the possibility of substitution on the nitrogen atom for further tuning of their optical and electronic properties. Benz[X]azole derivatives are interesting compounds with several optical applications,2 and as biologically active compounds.3